Impaired Muscle Regeneration in Ob/ob and Db/db Mice - Mai-Huong Nguyen; Ming Cheng; Timothy J. Koh (The Scientific World Journal)
In obesity and type 2 diabetes, efficient skeletal muscle repair following injury may be required, not only for restoring muscle structure and function, but also for maintaining exercise capacity and insulin sensitivity. The hypothesis of this study was that muscle regeneration would be impaired in ob/ob and db/db mice, which are common mouse models of obesity and type 2 diabetes. Muscle injury was produced by cardiotoxin injection, and regeneration was assessed by morphological and immunostaining techniques. Muscle regeneration was delayed in ob/ob and db/db mice, but not in a less severe model of insulin resistance – feeding a high-fat diet to wild-type mice. Angiogenesis, cell proliferation, and myoblast accumulation were also impaired in ob/ob and db/db mice, but not the high-fat diet mice. The impairments in muscle regeneration were associated with impaired macrophage accumulation; macrophages have been shown previously to be required for efficient muscle regeneration. Impaired regeneration in ob/ob and db/db mice could be due partly to the lack of leptin signaling, since leptin is expressed both in damaged muscle and in cultured muscle cells. In summary, impaired muscle regeneration in ob/ob and db/db mice was associated with reduced macrophage accumulation, angiogenesis, and myoblast activity, and could have implications for insulin sensitivity in the skeletal muscle of obese and type 2 diabetic patients.